2017
DOI: 10.1016/j.hal.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low-level exposure to the common seafood toxin domoic acid causes cognitive deficits in mice

Abstract: The consumption of one meal of seafood containing domoic acid (DA) at levels high enough to induce seizures can cause gross histopathological lesions in hippocampal regions of the brain and permanent memory loss in humans and marine mammals. Seafood regulatory limits have been set at 20 mg DA/kg shellfish to protect human consumers from symptomatic acute exposure, but the effects of repetitive low-level asymptomatic exposure remain a critical knowledge gap. Recreational and Tribal-subsistence shellfish harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 44 publications
3
38
1
Order By: Relevance
“…In both studies, the effect size of the memory decrement was small, and overall memory scores remained within normal limits. The findings were consistent with a controlled laboratory study in which weekly exposures to DA at subclinical levels for several weeks resulted in significant learning and memory deficits in mice [ 24 ]. While statistically significant and of academic interest, questions remain about the actual clinical significance of the mild memory decrement found in NAs who routinely consume a lot of RCs.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In both studies, the effect size of the memory decrement was small, and overall memory scores remained within normal limits. The findings were consistent with a controlled laboratory study in which weekly exposures to DA at subclinical levels for several weeks resulted in significant learning and memory deficits in mice [ 24 ]. While statistically significant and of academic interest, questions remain about the actual clinical significance of the mild memory decrement found in NAs who routinely consume a lot of RCs.…”
Section: Introductionsupporting
confidence: 90%
“…Within the context of the other findings, it also raises the possibility that some EM problems arise and persist for up to 10 to 14 days after exposure, then abate, though never fully to baseline level. The potential for reversibility of DA-related memory deficits in mice was previously demonstrated by Lefebvre et al [ 24 ]. Additionally, previously reported data referencing non-human primate and human models by Kumar et al [ 27 ], suggests a tolerable daily intake (TDI) of 0.075 ppm for gastrointestinal (GI) disturbances in humans.…”
Section: Discussionmentioning
confidence: 92%
“…The PBPK models also predicted a much longer duration of exposure in the brain following oral dosing than what is observed after intravenous dosing. This may be important for chronic toxicity of asymptomatic exposures to DA, that lead to the reported sensitization to DA and to epigenetic changes (Hiolski et al, 2014;Lefebvre et al, 2017). However, the current model does not incorporate possible transporter contributions to brain distribution of DA, which requires further study.…”
Section: Downloaded Frommentioning
confidence: 99%
“…However, information to establish a chronic TDI for DA is currently not available (Pulido, 2008). Several studies in model species have suggested that chronic low-level DA exposure at asymptomatic doses results in adverse effects, including epigenetic changes and sensitization of animals to the toxicity of DA (Hiolski et al, 2014;Lefebvre et al, 2017). Yet, the underlying mechanisms of these changes and DA toxicokinetics at asymptomatic doses have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental and neurological effects of chronic (low-level) DA exposure on infants and young children are a concern, as DA has been shown to cross the placenta, enter the blood brain barrier of infants, and collect in amniotic fluid in mammals [81][82][83][84][85]. Chronic DA exposure has also been linked to cognitive impairment in mice [86]. More reliable chronic DA exposure epidemiological studies on humans, however, have been rarely reported.…”
Section: Human Health Effectsmentioning
confidence: 99%